Hubungan Pengetahuan Dampak Seksual Pranikah dengan Gaya Pacaran Pada Remaja SMA GIKI 2 Surabaya Tahun 2022 - SITI NUR HIDAYAH; Purborini, Shintya Fitri Ayu; Salim, Lutfi Agus (Universitas Airlangga, 2025)
Background: The current dating style of teenagers is quite worrying because it has exceeded normal limits, such as premarital sexual behavior which has impacts such as unwanted pregnancy, sexually transmitted infections and even sexual violence. Lack of knowledge about the impact of premarital sex is one of the causes of sexual behavior. Reproductive Health Education as one of the efforts to provide knowledge about the impact of premarital sexual behavior on teenagers. Objectives: To determine the relationship between knowledge of the impact of premarital sexual relations and dating style among students at SMA GIKI 2 Surabaya. Methods: Analytical observation study with cross-sectional research design. The research sample was 60 students from 150 populations. The independent variable in this research is knowledge of the impact of premarital sex and the dependent variable in this research is the dating style of students at GIKI 2 High School Surabaya. The research was conducted in May 2022 using a questionnaire research instrument. The analysis used in this research was the Spearman rank correlation test analysis. Results: Gender with knowledge about the impact of premarital sex has a relationship with a p-value =0.031 (<0.05) with a relationship strength of 0.279. The results of this study indicate that there is a relationship between knowledge about the impact of premarital sex and students' dating styles because p-value=0.000 (<0.05) with a relationship strength of -0.464. Conclusions: There is a relationship between knowledge about the impact of premarital sexual relations and dating styles among students at SMA GIKI 2 Surabaya. Students who have higher knowledge do not have a risky dating style, while students who have low knowledge will have a risky dating style.Teenagers who have low knowledge should be given premarital sexual education so that they can avoid premarital sexual behavior.